Anthropometric assessment of the elite Italian female volleyball players: a comparison among roles - Benelli, P.; Del Sal, M.; Di Paoli, A,.; Ditroilo, M.; Grassi, E.; Lucertini, F.; Piatti, G.; Stocchi, V. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction The correct identification of performance features of high level athletes, taking into consideration not only the large variety of sports but also the different roles in the same game, is pivotal for athletes, coaches and researchers. In the last thirty years anthropometric and body composition measures have received a lot of attention from the scientific community, as they are used during athletes selection phase and have a relationship with technical level of performance. Recent studies conducted on volleyball have found that in both male and female world class athletes, the average height tends to increase and the average percentage of body fat is optimized. Yet, very few studies have emphazised the difference of anthropometric measurements and body composition among players of different roles in the same game. In volleyball, the new FIVB rules have recently introduced a new player: the 'libero' position. To our knowledge, no studies have been conducted to assess this new role. The purpose of this study was to examine anthropometric and body composition values in top level women volleyball players, and to analyse general trend and any possible differences among roles. Methods The subjects were 19 members of the Italian women`s 2002 world champion volleyball team. Height and weight were measured with a telescopic rod and medical scales respectively (Seca) and the BMI was subsequently calculated. Seven skinfolds thickness were measured using a Harpenden skinfold caliper: biceps, triceps, subscapular, suprailiac, chest, thigh, abdominal. Body density (and percentage of body fat) was calculated according to Durnin/Womersley (4 skinfold thickness) and Jackson/Pollock (4 skinfold thickness and age). A Multi Frequency Segmental Bioelectrical Impedance Analysis (Human-Im Plus, DS Medigroup, Italy) was conducted in order to assess body composition according to Segal equation. Discussion/Conclusion Our results and previous studies suggest that in high level athletes, height shows an increasing trend whilst percentage of body fat tends to decrease, although the methods to assess this variable are quite different. We have shown the differences among roles, although no statistics were calculated because of the small, non-random nature of the groups involved. Yet, the "libero" position, introduced by the new rules quite recently, seems to have peculiar characteristics. For instance, our results show a much smaller height and weight compared to other roles. If this is confirmed in future studies with more high level libero players, this fact should be taken into consideration for talent identification and the definition of the relationship between anthropometric characteristics and performance.